Home Schooling sebagai Pendidikan Alternatif Proses Belajar-Mengajar dalam Pendidikan - Ade Muslimat (Jurnal Studi Gender dan Anak, 2017)
Homeschooling or Home School (also called home education or home based learning) is the education of children at home, typically by parents or by tutors, rather than in other formal settings of public or private school. Although prior to the introduction of compulsory school attendance laws, most childhood education occurred within the family or community, homeschooling in the modern sense is an alternative in developed countries to attending public or private schools. Homeschooling is a legal option for parents in many countries, allowing them to provide their children with a learning environment as an alternative to public or private school outside the home. Parents cite three main reasons for homeschooling their children dissatisfaction with the local schools and the interests in increased involvement with their children’s learning and development. To provide a specific religious or moral instruction and dissatisfaction with available school environment the quality of academic instruction, the curriculum.Recently, home school has increased popularity in Indonesia of children ages 5 through 17 who are homeschooled increased from 2002 to 2015.